Professionalism among nurses working in a tertiary hospital - KC, Sarala; Samson, Priscilla; Dangol Shrestha, Shanta; Shrestha, Rachana; Rongong, Anita (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Professionalism in nursing practice ensures safety and quality patient care. A high level of professionalism is essential for developing professional identity. The purpose of this study was to find out the nurses’ professionalism and professional identity. Method: A cross sectional analytical study was conducted in September 2021 among nurses of Patan Hospital. Data were collected using Snizek-Revised Professionalism Inventory and Adam’s Professional Identity Scale via online Google form and printed forms. Spearman’s rho test was used to analyze the correlation between professionalism and professional identity. The associations of professionalism and professional identity with personal characteristics of nurses were measured by Pearson’s Chi-square test. Result: A total of 386 nurses participated in the study. Of the participants, only 181(46.95%) had a membership in any nursing professional organization. A high level of professionalism was perceived by 205(53.1%) with the highest mean score (16.9±3.20) for sense of calling to nursing profession and the lowest mean score (15.94±3.31) for using professional organization as a major referent. Most nurses 211(54%) perceived a high level of professional identity. A positive significant correlation was found between professionalism and professional identity (p<0.01). Age (p=0.02) and nursing title (p=0.03) had a significant association with professional identity. Conclusion: More than half participants had a high level of professionalism and professional identity. There was a positive significant correlation between professionalism and professional identity. No significant association between personal factors and professionalism; however, age and nursing job title were significantly associated with professional identity.